Masks Start to Drop: Suppressor of MAX2 1-Like Proteins Reveal Their Many Faces - Temmerman, Arne; Guillory, Ambre; Bonhomme, Sandrine; Goormachtig, Sofie; Struk, Sylwia (Frontiers in Plant Science, 2022)
Although the main players of the strigolactone (SL) signaling pathway have been characterized genetically, how they regulate plant development is still poorly understood. Of central importance are the SUPPRESSOR OF MAX2 1-LIKE (SMXL) proteins that belong to a family of eight members in the Arabidopsis thaliana genome, of which one subclade is involved in SL signaling and another one in the pathway of the chemically related karrikins. Through proteasomal degradation of these SMXLs, triggered by DWARF14 (D14) and KARRAKIN INSENSITIVE2 (KAI2), respectively, several physiological processes are controlled, such as, among others, shoot and root architecture, seed germination, and seedling photomorphogenesis. Yet another clade has been shown to control phloem development and anthocyanin production, independently of the D14 and KAI2 actions and not relying on proteasomal degradation. Despite their importance throughout plant development, the precise molecular mechanisms by which SMXLs regulate these processes are far from completely unraveled. To fill the major knowledge gap in understanding D14 and KAI2 signaling, SMXLs are intensively studied, making it challenging to combine all the insights into a coherent characterization of these important proteins. To this end, this review provides an in-depth exploration of the recent data regarding their physiological function, evolution, structure, and molecular mechanism. In addition, we suggest a selection of future perspectives, focusing on the still underappreciated apparent localization of SMXLs in nuclear speckles and on recent advances in the field of biomolecular condensates and liquid-liquid phase separation.